Chalcogen‐Bonding Catalysis with Telluronium Cations. Issue 35 (20th July 2021) - Weiss, Robin; Aubert, Emmanuel; Pale, Patrick; Mamane, Victor
Abstract: Chalcogen bonding results from non‐covalent interactions occurring between electrodeficient chalcogen atoms and Lewis bases. Among the chalcogens, tellurium is the strongest Lewis acid, but Te‐based compounds are scarcely used as organocatalysts. For the first time, telluronium cations demonstrated impressive catalytic properties at low loadings in three benchmark reactions: the Friedel–Crafts bromination of anisole, the bromolactonization of ω‐unsaturated carboxylic acids and the aza‐Diels–Alder between Danishefsky's diene and imines. The ability of telluronium cations to interact with a Lewis base through chalcogen bonding was demonstrated on the basis of multi‐nuclear ( 17 O, 31 P, and 125 Te) NMR analysis and DFT calculations. Abstract : New telluronium salts exhibit enhanced properties due to the presence of 3 σ‐holes. This is highlighted in solution by Ph3 PO‐binding studies through 17 O, 31 P, and 125 Te NMR as well as mass spectrometry and NOESY NMR. The enhanced chalcogen‐bonding properties translated into high catalytic performance, with low loadings (0.5–5 mol %), short reaction times (5 min–2 h), and high yields.